Autopilot design for bank-to-turn missiles under command to line-of-sight guidance - 429304 Loh, Soo Hau (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001